Effect of plastic deformation on compliance curve based crack closure measurement - Mohin, M.; Xu, Yigeng; Lewis, A.; Chrysanthou, A. (Trans Tech Publications, 2016)
Fatigue crack growth depends heavily on near tip stress-strain behavior controlled by many micromechanical and microstructural factors. Crack closure is widely used to rationalize crack growth behaviour under complex loading conditions. Reliable crack closure measurement is essential for enhanced damage tolerance design and remains a challenge to the industry. This paper focuses on the effect of plastic deformation ahead of a notch/crack on the non-linearity of compliance curves of 6082-T651 aluminium alloy specimens to highlight a potential issue in the conventional compliance curve based crack closure measurement technique. Experimental and numerical simulation results demonstrate that plastic deformation ahead of the notch will introduce non-linear stress-strain behavior in the absence of crack closure. It is proposed that the effect of crack tip plasticity on the non-linearity of the compliance curve be separated to obtain reliable crack closure measurement.
Keywords: Compliance curve; Crack closure; Damage tolerance design